Inequality in environmental risk exposure and procedural justice in the Matanza-Riachuelo River Basin - Mitchell, Ann Elizabeth (2024)
Fil: Mitchell, Ann Elizabeth. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación; Argentina